Prenatal and postnatal exposure to NO2 and child attentional function at 4–5 years of age - Sentís, Alexis; Sunyer, Jordi; Dalmau-Bueno, Albert; Andiarena, Ainara; Ballester, Ferran; Cirach, Marta; Estarlich, Marisa; Fernández-Somoano, Ana; Ibarluzea, Jesús; Íñiguez, Carmen; Lertxundi, Aitana; Tardón, Adonina; et al. (Environment international, 2017)
BACKGROUND: Prenatal and postnatal exposure to air pollution has been linked to cognitive impairment in children, but very few studies have assessed its association with attentional function. OBJECTIVES: To evaluate the association between prenatal and postnatal exposure to nitrogen dioxide (NO2) and attentional function in children at 4-5years of age. METHODS: We used data from four regions of the Spanish INMA-Environment and Childhood-Project, a population-based birth cohort. Using land-use regression models (LUR), we estimated prenatal and postnatal NO2 levels in all of these regions at the participants' residential addresses. We assessed attentional function using the Kiddie-Conners Continuous Performance Test (K-CPT). We combined the region-specific adjusted effect estimates using random-effects meta-analysis. RESULTS: We included 1298 children with complete data. Prenatal exposure to NO2 was associated with an impaired standard error of the hit reaction time (HRT(SE)) (increase of 1.12ms [95% CI; 0.22 a 2.02] per 10μg/m3 increase in prenatal NO2) and increased omission errors (6% [95% CI; 1.01 to 1.11] per 10μg/m3 increase in prenatal NO2). Postnatal exposure to NO2 resulted in a similar but borderline significant increase of omission errors (5% [95% CI; =0.99 to 1.11] per 10μg/m3 increase in postnatal NO2). These associations did not vary markedly between regions, and were mainly observed in girls. Commission errors and lower detectability were associated with prenatal and postnatal exposure to NO2 only in some regions. CONCLUSIONS: This study indicates that higher exposure to ambient NO2, mainly during pregnancy and to a lesser extent postnatally, is associated with impaired attentional function in children at 4-5years of age. This study was funded by grants from the Instituto de Salud Carlos III (Red INMA G03/176; CB06/02/0041 and PI031615; PI041931; PI041112; PI041436; PI041509; PI042018; PI051079; PI051052; PI060867; PI061213; PI070314; CP1100178; PI081151 incl. FEDER funds; PS0900090 incl. FEDER funds; PI0902311 incl. FEDER funds; PI0902647 incl. FEDER funds; PI1102591 incl. FEDER funds; PI1102038 incl. FEDER funds; PI131944 incl. FEDER funds; PI132032 incl. FEDER funds; PI1302429 incl. FEDER funds; PI1302187 incl. FEDER funds; PI140891 incl. FEDER funds; PI141687 incl. FEDER funds and MS13/00054), Generalitat de Catalunya-CIRIT 1999SGR 00241, Fundació La marató de TV3 (090430), Department of Health of the Basque Government (2005111093, 2009111069 and 2013111089), the Provincial Government of Gipuzkoa (DFG06/002 and DFG08/001), Convenios anuales con los ayuntamientos de la zona del estudio (Zumarraga, Urretxu, Legazpi, Azkoitia y Azpeitia y Beasain), from UE (FP7-ENV-2011 cod 282957 and HEALTH.2010.2.4.5-1), from the European Research Council under the ERC Grant Agreement number ERC-AdG 2010 GA#268479 – the BREATHE project, from the Conselleria de Sanitat of Generalitat Valenciana (AP212/11, 002/008, 012/009, 013/2009, 014/009, 015/008, 016/009, 021/007, 021/008, 023/008 and 024/007) and from Obra Social Cajastur/Fundación Liberbank and Universidad de Oviedo. ISGlobal is a member of the CERCA Programme, Generalitat de Catalunya